2015
DOI: 10.1007/s13349-015-0129-4
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to an FBG-based inclinometer and its application to landslide monitoring

Abstract: This paper presents a self-designed in-place inclinometer based on fiber Bragg grating (FBG) technology and introduces its application to a landslide monitoring project in Wenzhou, China. The working principle of the FBG-based inclinometer is briefly introduced. The FBG-based inclinometers were installed into nine boreholes that were distributed over different areas of the landslide. After 4 months of monitoring, the deformation of the soil mass at different depths above the bedrock within the landslide was ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 16 publications
0
29
0
Order By: Relevance
“…The integral method was utilized to calculate the displacements in different depths based on linear interpolation of strain distribution along the PVC casing. Wang et al successfully installed this inclinometer in nine boreholes for landslide monitoring in Wenzhou, China [50]. The slip surface determined by the monitoring results fit well with that calculated by limit equilibrium method.…”
Section: Development Of Fbg-based Geohazard Monitoring Systemsmentioning
confidence: 62%
See 1 more Smart Citation
“…The integral method was utilized to calculate the displacements in different depths based on linear interpolation of strain distribution along the PVC casing. Wang et al successfully installed this inclinometer in nine boreholes for landslide monitoring in Wenzhou, China [50]. The slip surface determined by the monitoring results fit well with that calculated by limit equilibrium method.…”
Section: Development Of Fbg-based Geohazard Monitoring Systemsmentioning
confidence: 62%
“…However, long-term use of inclinometers is impractical due to the disadvantages of low accuracy, poor durability, complex operation, and high costs. In recent years, several studies of in-place slope displacement monitoring using FBG-based techniques have been reported [15,16,47,48,49,50]. Figure 4 shows the typical structures of FBG in-place inclinometers.…”
Section: Development Of Fbg-based Geohazard Monitoring Systemsmentioning
confidence: 99%
“…Since the early 1990s, FBG sensing technology has been developed in several universities in China, such as Tsinghua University, Chongqing University, Wuhan University of Technology, Harbin Institute of Technology, Tianjin University, Chinese Academy of Sciences and so on. FBG sensors have been applied in many fields, like bridge health monitoring, high temperature and high pressure sensing in oil well and seismic detection [31][32][33][34]. Besides, Liu etc.…”
Section: Fiber Bragg Grating (Fbg) Fiber Optic Sensorsmentioning
confidence: 99%
“…Slope instability is considered to be closely related to slope deformation [ 22 ]. Accordingly, FBG-based inclinometers were designed to measure internal displacement and locate the slip surface by analyzing displacement data [ 23 , 24 ]. However, the detectable displacement is the result of strain accumulation within the soil mass.…”
Section: Introductionmentioning
confidence: 99%